Happiness and well-being in Chinese societies : sociocultural analyses - Cheung, Chau-kiu (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book addresses the sustainability of happiness and well-being in Chinese societies. It starts by introducing the various conceptions of well-being, particularly in Chinese sociocultural context. The book then proceeds with the examination of the sustainability of well-being by scrutinizing the effects of sociocultural contextual and personal factors on well-being. The contextual factors are the aggregates or averages of personal factors at the contextual levels of the region and college in Mainland China, its special administrative region, and Taiwan. These factors cover personality traits, strengths, orientations, beliefs, values, and idolizing. By bringing together empirical studies and theoretical perspectives applied to Chinese societies, this book offers researchers in social science and humanities a valuable reference work on happiness and well-being in Chinese societies"--
OCLC-licensed vendor bibliographic record.
Keywords: Well-being -- China; Well-being -- Taiwan; Happiness -- China; Happiness -- Taiwan; Quality of life -- China; Quality of life -- Taiwan; China -- Social life and customs; PSYCHOLOGY / General